Spatially-resolved studies on the role of defects and boundaries in electronic behavior of 2D materials. Issue 3 (August 2017) - Hus, Saban M.; Li, An-Ping
Abstract: Two-dimensional (2D) materials are intrinsically heterogeneous. Both localized defects, such as vacancies and dopants, and mesoscopic boundaries, such as surfaces and interfaces, give rise to compositional or structural heterogeneities. The presence of defects and boundaries can break lattice symmetry, modify the energy landscape, and create quantum confinement, leading to fascinating electronic properties different from the "ideal" 2D sheets. This review summarizes recent progress in understanding the roles of defects and boundaries in electronic, magnetic, thermoelectric, and transport properties of 2D layered materials. The focus is on the understanding of correlation of atomic-scale structural information with electronic functions by interrogating heterogeneities individually. The materials concerned are graphene, transition metal dichalcogenides (TMDs), hexagonal boron nitride (hBN), and topological insulators (TIs). The experimental investigations benefit from new methodologies and techniques in scanning tunneling microscopy (STM), including spin-polarized STM, scanning tunneling potentiometry (STP), scanning tunneling thermopower microscopy, and multi-probe STM. The experimental effort is complemented by the computational and theoretical approaches, capable of discriminating between closely competing states and achieving the length scales necessary to bridge across features such as local defects and complex heterostructures. The goal is to provide a general view of current understanding and challenges in studying the heterogeneities in 2D materials and to evaluate the potential of controlling and exploiting these heterogeneities for novel functionalities and electron devices.